TANTAGAN DAN SOLUSI SISTEM PENGELOLAAN DANA PENDIDIKAN DI ERA DIGITAL - Sabeni; Suherman, Ujang; Apriliantoni (LPPM STAI Muhammadiyah Probolinggo, 2025)
Management of education funds is the most important and strategic element in realizing equal access and improving the quality of education in Indonesia. This research aims to identify the main challenges and solutions in managing education funds in Indonesia. The method in this research uses a qualitative approach based on literature studies. This study analyzes various relevant scientific journals, and compares fund management systems in several regions in Indonesia and developed countries such as Finland and Singapore. The results of this research show that the management of education funds in Indonesia still faces major challenges, especially in terms of uneven distribution, low transparency and suboptimal efficiency. Digitalization of the transparency system, enforcement of regulations, and involvement of local communities have proven to be effective strategies for improving the management of education funds.